INFLUENCE OF N AND K RATES ON YIELD AND QUALITY OF CHIPPING VARIETY KUFRI CHIPSONA-3 - Kumar, Parveen; Pandey, S K; Singh, S V; Kumar, Dinesh; Singh, B P; Singh, Sukhwinder; Rawal, S; Meena, R L (Potato Journal, 2013)
Â Â